Penggunaan Metode Kubaca untuk Meningkatkan Kemampuan Memahami Kata Anak Usia Dini Raudhatul Athfal - Istianah; Mundir (HMPS PIAUD FTIK IAIN Jember, 2021)
The ability to read at an early age greatly affects the level of intelligence of children. The earlier a child learns to read, the more fond he is to read and the better he will read. So parents and teachers should teach children to read from an early age. Because the ability to read is the basis for mastering various sciences. The purpose of this study was to analyze and describe the steps of implementing the